BRUTE FORCE ATTACK – BLOCKING TECHNIQUE (International Journal of Engineering and Computer Science, 2017)
A common threat Web developers face is a password-guessing attack known as a brute-force attack. A brute-force attack is an attempt to discover a password by systematically trying every possible combination of letters, numbers, and symbols until you discover the one correct combination that works. If your Web site requires user authentication, you are a good target for a brute-force attack. An attacker can always discover a password through a brute-force attack, but the downside is that it could take years to find it. Depending on the password's length and complexity, there could be trillions of possible combinations. To speed things up a bit, a brute-force attack could start with dictionary words or slightly modified dictionary words because most people will use those rather than a completely random password. These attacks are called dictionary attacks or hybrid brute-force attacks. Brute-force attacks put user accounts at risk and flood your site with unnecessary traffic. Hackers launch brute-force attacks using widely available tools that utilize wordlists and smart rule set to intelligently and automatically guess user passwords. Although such attacks are easy to detect, they are not so easy to prevent